PENINGKATAN KINERJA KARYAWAN MELALUI PENGEMBANGAN DIRI PADA CHIP PROFESIONAL KOMPUTER PEKANBARU - Nurul, Nurul; Marlinda, Marlinda (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Abstract: Self-development is a crucial element in improving employee performance, particularly in service-based MSMEs. Chip Profesional Komputer faces issues of motivation, communication, and time management that impact service quality. This community service activity was conducted through outreach activities that included positive work attitudes, effective communication, time management, and simple performance evaluations. The results of the activity demonstrated an increased understanding among employees regarding the importance of friendly communication, discipline, and continuous self-development. This activity also created opportunities for management to implement regular training and performance evaluations. Self-development, employee performance, communication, work discipline.